The Spanish submission for extension of the Canary Islands continental shelf: Spain and Morocco face each other in a new ring - Jiménez García-Carriazo, Ángeles (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2024)
In 2014, Spain made a submission to the Commission on the Limits of the Continental Shelf (CLCS or Commission) for the area to the west of the Canary Islands. The submission anticipated potential overlaps with neighbouring territories, namely, Portugal and Western Sahara. Pending consideration by the CLCS, Madrid shifted its policy towards the dispute in Western Sahara in 2022. The historic stance change may strip away the rules of the game for the extension, subject always to check and balances beyond its technical nature.